2019
DOI: 10.1108/jeim-04-2019-0105
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between task characteristics and technology affordances

Abstract: Purpose Enterprise social media (ESM) usage has gained considerable momentum within organizations. The purpose of this paper is to seek a better understanding of ESM usage based on the task environments and the technology affordances of ESM. Design/methodology/approach This study is based on a survey consisting of 556 usable responses. Regression methods are applied to analyze the data. Findings This study finds strong support for the positive impact of task-technology fit on ESM usage. Considering separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…It means that TTF emphasizes that the accuracy of the implementation of tasks and information technology will support the performance of individuals in the company. Task-technology fit refers to matching the technology capabilities with the job requirements, namely, the ability of technology to support a task (Teo & Men, 2008;Fu et al, 2019). Goodhue and Thompson (1995) proposed the TTF model, which extends the TAM by considering how a task affects the use of technology (Tam & Oliveira, 2016).…”
Section: Task Technology Fit (Ttf)mentioning
confidence: 99%
“…It means that TTF emphasizes that the accuracy of the implementation of tasks and information technology will support the performance of individuals in the company. Task-technology fit refers to matching the technology capabilities with the job requirements, namely, the ability of technology to support a task (Teo & Men, 2008;Fu et al, 2019). Goodhue and Thompson (1995) proposed the TTF model, which extends the TAM by considering how a task affects the use of technology (Tam & Oliveira, 2016).…”
Section: Task Technology Fit (Ttf)mentioning
confidence: 99%
“…Task characteristics affect employee use of organizational information systems. For instance, Fu et al (2019) found that task interdependence with ESM fit significantly impacts ESM use of employees. Task interdependence (Lin and Huang, 2008) and task complexity (Koo et al , 2011) are also found to promote employee use of organization information systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Schneckenberg (2009) argued that the potential of ESM to act as a lever for organization learning and knowledge sharing depends largely on the degree of openness, freedom and employee empowerment in the enterprise environment. Furthermore, Fu et al (2020) found that task-technology fit had a positive effect on ESM usage, and task interdependence had a negative effect on ESM usage.…”
Section: Analysis Of Landmark Research In the Esm Literaturementioning
confidence: 97%